A Decode Technique of MSI for Efficient Reconstruction Process - Narmatha, C; Manimegalai, P; Manimurugan, S; Almutairi, Saad; Aborokbah, Majed (International Journal of Engineering and Technology, 2018)
This paper presents aMSI(Modified Steganography for Image) decode technique for the perfect reconstruction process. Many algorithms are failing in decoding process due to the various reasons. In order to overcome those issues, an efficient decode process of MSI has been proposed in this paper presents. Basically, theMSImethod can be classified into two parts of Encode and Decode. The segregation process for constructing the subbands,8-bit binary conversion process, Inverse substitution process and Decimal conversion process are doing an important role inMSIdecode process. In addition, to measure theMSIdecode performances, the standard parameters are used. This technique is designed mainly for the secret medical image transmission. The secret input image pixels should not be loss while transmitting over the network. In case of loss, itâ€™s very hard to retrieve the original secret image/date during the reconstruction process. This issue has been addressed byMSIdecode process. In result, the original secret image can be restored 100% from this technique, the decode time is minimum than the conventional methods, the replica of the cover or known image can be obtained. However, the main advantages of this technique are easy to handle, more complex and strength than other methods, a perfect reconstruction without any loss and less execution time.Â Â